2013
DOI: 10.1126/science.1229566
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Personal Genomes by Surname Inference

Abstract: Sharing sequencing data sets without identifiers has become a common practice in genomics. Here, we report that surnames can be recovered from personal genomes by profiling short tandem repeats on the Y chromosome (Y-STRs) and querying recreational genetic genealogy databases. We show that a combination of a surname with other types of metadata, such as age and state, can be used to triangulate the identity of the target. A key feature of this technique is that it entirely relies on free, publicly accessible I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
701
0
9

Year Published

2013
2013
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 970 publications
(712 citation statements)
references
References 23 publications
(2 reference statements)
2
701
0
9
Order By: Relevance
“…Interestingly, there was little evidence of fear of results or implications for insurance, employment or privacy being a potential barrier to participation in genomics research: only one person stated that their reason for being unwilling to participate in genomics research was that they would be "scared to know," and only one person's reason for being unwilling appeared to be linked to concern about the potential for loss of privacy, saying "once information is out, it goes out all over." We speculate that this may perhaps be due to low awareness of the possible implications for insurance and employment (Dorsey et al 2012), low relevance of these issues given the low income of many of these patients, or low awareness of the current evidence indicating the inherent impossibility of guaranteeing privacy of personal genomic information once donated to genomics research (McEwen et al 2013;Gymrek et al 2013). Alternatively, it could reflect a genuine lack of fear or concern regarding these issues.…”
Section: Discussionmentioning
confidence: 96%
“…Interestingly, there was little evidence of fear of results or implications for insurance, employment or privacy being a potential barrier to participation in genomics research: only one person stated that their reason for being unwilling to participate in genomics research was that they would be "scared to know," and only one person's reason for being unwilling appeared to be linked to concern about the potential for loss of privacy, saying "once information is out, it goes out all over." We speculate that this may perhaps be due to low awareness of the possible implications for insurance and employment (Dorsey et al 2012), low relevance of these issues given the low income of many of these patients, or low awareness of the current evidence indicating the inherent impossibility of guaranteeing privacy of personal genomic information once donated to genomics research (McEwen et al 2013;Gymrek et al 2013). Alternatively, it could reflect a genuine lack of fear or concern regarding these issues.…”
Section: Discussionmentioning
confidence: 96%
“…The recent revelation that it is possible to identify individuals on the basis of their "deidentified" genomic data serves as a case in point. 26 There was widespread negative reaction and alarm despite the fact that no negative consequences befell those who were reidentified. 27 The bare fact that these individuals were reidentified ("unclothed, " so to speak) itself constituted the harm.…”
Section: Beyond the Consequencesmentioning
confidence: 99%
“…Third, it has been demonstrated that failsafe de-identification of human genomic data is not possible. 7 A fourth point is that genomic sequencing methods have co-evolved with powerful tools for manipulating and sharing these data in large bio-repositories and databases. The relative ease of sharing data among investigators underscores a need to modernize guidelines for using these data in research now that it can be linked to the individuals who contributed it more readily.…”
Section: Introductionmentioning
confidence: 99%